ANALISIS POTENSI PELANGGARAN HAM PADA KASUS POLITIK UANG (MONEY POLITICS) PEMILU DALAM PERSPEKTIF KAJIAN POLITIK HUKUM - Dewi Safitri; M. Heriyanto, M. Agung Soleh, Yusuf Setyadi, Sugianto (INTELIGENSIA MEDIA, 2025)
The crime of money politics in the context of the General Election (Pemilu) in Indonesia is regulated in Article 523 of Law No. 7 of 2017. This article divides the crime of money politics into three categories, namely during the campaign, the quiet period, and during voting, each of which has the same actus reus elements. The mens rea element in this crime is formulated by prioritizing intent, which shows that the perpetrator committed the act with a specific purpose. The criminal sanctions regulated in the article use the indefinite sentence pattern, namely the threat of a criminal sentence that does not have a specified time period. However, a more appropriate criminal threat model is the indeterminate sentence, which provides flexibility in determining the sentence based on consideration of the situation and condition of the perpetrator and his role in the crime. Prevention of the crime of money politics can be done by adopting the doctrine of crime prevention from a criminological perspective, which consists of five main theories. First, the abolitionist theory which emphasizes the factors that drive crime. Second, the moralistic theory which focuses on enlightening society through the spread of moral messages. Third, the primary prevention theory, which seeks to prevent crimes before they occur, as well as secondary and tertiary prevention theories that focus more on efforts after the crime has occurred, both in the form of rehabilitation and mitigation of the impact of the crime. In addition, political parties involved in the crime of money politics must be held criminally liable. This can refer to the identification theory, which states that political parties are responsible for the actions of their members during the election process, especially if the party is involved in the practice of money politics.